Faktor-Faktor Yang Mempengaruhi Pembiayaan Murabahah Di Lembaga Keuangan Syariah (Studi Kasus KSPPS BMT Assyafi’iah Berkah Nasional Cabang Kotagajah) - Wuri, Sela Prela; Ali, Karnila (Universitas Muhammadiyah Metro, 2022)
This study aims to determine how the factors of internal information in the form of Financing To Deposit Ratio (FDR), Return On Assets (ROA), Third Party Funds (DPK), Non Performing Financing (NPF). The object of this research was conducted at KSPPS BMT Assyafi'iyah Berkah Nasional Kotagajah Branch. This study uses a quantitative approach, the data used is primary data, namely financial reports per semester obtained directly from KSPPS BMT Assyafi'iyah Berkah Nasional Kotagajah Branch. The sample used in this study is the financial report per semester of KSPPS BMT Assyafi'iyah Berkah Nasional Kotagajah Branch for the 2018-2020 period. The data analysis method used is multiple regression analysis by testing the classical assumptions first. The hypothesis test carried out is a partial test or t test and a simultaneous test or f test with a significance level of 5%. Based on the observation period, it shows that the research data is normally distributed. The results of the autocorrelation test, multicollinearity test and heteroscedasticity test did not find variables that deviated from the classical assumption rules. The results of the hypothesis test show that partially the Financing To Deposit Ratio (FDR) variable with a significant value of 0.002 and Third Party Funds (DPK) with a significant value of 0.006, has a positive and significant effect on the distribution of KSPPS BMT Assyafi'iyah Berkah Nasional Kotagajah financing and Return On Assets (ROA) with a significant value of 0.088 and Non Performing Financing (NPF) with a significant value of 0.132 have a negative and significant effect. While the results of the simultaneous test show that the variables of Financing To Deposit Ratio (FDR), Return On Assets (ROA), Third Party Funds (DPK), Non Performing Financing (NPF) have a significance value of 0.004 Keywords : FDR, ROA, DPK, NPF, and Murabahah Financing.